PENGARUH PEMBERIAN PUPUK ORGANIK CAIR CANGKANG TELUR AYAM TERHADAP PERTUMBUHAN VEGETATIF BAYAM MERAH (Amaranthus tricolor L.) - Fitri Rahmadani Batubara (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
Chicken egg shell is one of the ingredients that can be used as liquid organik fertilizer, because chicken egg shells have a lime substitute to increase soil pH. The purpose of this research is to investigate the effect of giving chicken egg shell liquid organik fertilizer on vegetative growth. Red spinach (Amaranthus tricolor L.)â€. Also to determine the effect of the amount of chlorophyll content of red spinach (Amaranthus tricolor L.) on the application of liquid organik fertilizer chicken egg shells. The experimental design used a completely randomized design (CRD). By giving treatment with 5 levels, namely 0%, 20%, 40%, 60% and 80%. The results showed that the application of different concentrations of liquid organik fertilizer on chicken egg shells had a significant effect on the growth of red spinach. Application of liquid organik fertilizer with concentrations of 60% and 80% is the most effective concentration. The amount of chlorophyll content in red spinach plants also showed a significant effect.